The Managerial Values, and Their Relationship with Some Facrtors That Concern The Managers and Their Performanc : A Fileld Study on The Banks branches' Managers ( Benghazi) - Al-Mula, Dr.abdulrahman; younis, Mr.Adel (Dirasat in Economics and Business, 2002)
The present study tride to highlight the managerial values footwork and their relatioship with some factors that concern the managers and their performance. It stems from the fact that values reprent one of the most important cultural facts that direct the human behavior and, consequeutly, its results. Data was collected through a questionnair distributed to 26 managers who run the banks acting in Benghazi. The study has resulted into the fact that the five value groups (according to buchholz classification ) are found characterizing the managers in rarious degrees of imþortance, Generally , they can be ranked as follows : l . The human values The organizational values, The job ethical values, The group cooperative values, and Rest and leisure time values. The framework of these values has varied according to soum characteristics of managers. In addition , the nature of the relationship of these values with the managers performance has varied .